1998
DOI: 10.1021/ma981114m
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched Poly(ether ketone) with Carboxylic Acid Terminal Groups:  Synthesis, Characterization, and Derivatization

Abstract: A new procedure is described for the formation of a hyperbranched poly(ether ketone) with carboxylic acid terminal groups. This preparation was based on the one-step synthesis of an AB2-type monomer 5-phenoxyisophthalic acid using phosphorus pentoxide/methanesulfonic acid as the condensing agent and solvent. The electrophilic aromatic substitution reaction led to the formation of the aryl ketone linkage. With the help of model compounds, 1H NMR studies revealed that the degree of branching of the poly(ether ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 45 publications
1
38
0
Order By: Relevance
“…However, because the aliphatic polyester possesses low thermal stability and modulus, these systems showed significant compromise in either T g or modulus. Recently, a plethora of heat-resistance HBPs, such as hyperbranched PEK [7,9,[19][20][21], ether imide [10,[22][23][24][25][26][27], aromatic polyester [4,28] and aromatic polyamide [8,29,30], have been reported. Despite this great variety, no study on the toughening of epoxy or BMI resin with any of these HBPs has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, because the aliphatic polyester possesses low thermal stability and modulus, these systems showed significant compromise in either T g or modulus. Recently, a plethora of heat-resistance HBPs, such as hyperbranched PEK [7,9,[19][20][21], ether imide [10,[22][23][24][25][26][27], aromatic polyester [4,28] and aromatic polyamide [8,29,30], have been reported. Despite this great variety, no study on the toughening of epoxy or BMI resin with any of these HBPs has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…These synthetic strategies were further extended for the preparation of hb poly(aryl ether)s in one-step polymerization from AB 2 monomers containing a phenolic group and two aryl fluorides, which were activated toward nucleophilic displacement by a sulfone, ketone, imide, or heterocycle [63][64][65]. Miller et al [63], Hawker and Chu [65], and Shu and Leu [66] reported the synthesis of hb poly(aryl ether ketone)s (hb-PAEKs) via the AB x method. The structures of AB 2 monomers reported by Hawker and Chu [65] are shown in Scheme 4 (1-5 and 1-6).…”
Section: Synthesis Of Aromatic Hyperbranched Polymersmentioning
confidence: 99%
“…The structures of AB 2 monomers reported by Hawker and Chu [65] are shown in Scheme 4 (1-5 and 1-6). The structures of AB 2 monomers reported by Shu and Leu [66] are shown in 1-7, Scheme 4.…”
Section: Synthesis Of Aromatic Hyperbranched Polymersmentioning
confidence: 99%
“…In the case of hyperbranched poly(aryl ether ketone), many strategies have been developed to prepare the polymers with highly branched structure, especially the convenient and cheap one-step polycondensation of AB X monomer has received significant attention. [21][22][23] However, all AB X monomer are unavailable commercially, which is potentially problematic, especially on a large scale. In addition, the manipulation of hyperbranched poly(ether ketone) structure completely depends on the variety of AB X monomer.…”
Section: Introductionmentioning
confidence: 99%